Experimental and Numerical Study on the Vortical Flow of MULDICON Wing Configuration - Ibrahim Madan; Jiun-Jih Miau; Shabudin Bin Mat (International Journal of Aerospace Engineering)
This paper highlights the results and comparison of the flow topology investigation above the unmanned combat aerial vehicle (UCAV) configuration, namely, multidisciplinary design configuration (MULDICON), with modified leading-edge profile at the apex region from a sharp to a blunt profile to reduce the complexity of the flow structure above the wing. It was found from the flow visualization results that at a low angle of attack, for instance, 10°, the onset of the flow separation took place near the apex region; the onset of a tip vortex at the wing tip was also detected. At a medium angle of attack, for instance, 15°, the onset of the flow separation moved further upstream with the formation of the apex vortex, and the magnitude of the tip vortex increased due to increasing incoming flow with increasing the angle of attack. At higher angle of attack, for instance, 20°, the apex vortex intensity increased and wing tip vortices shedding is observed. Furthermore, at an angle of attack of 25°, the configuration is partially stalled, while a complete stalled occurred at an angle of attack of 30°. The current results obtained from this study have shown that the configuration has a maximum lift coefficient of 0.8 obtained from the K-Omega-SST turbulence model while it is 0.93 calculated from the Spalart-Allmaras turbulence model, while the maximum drag coefficient is 0.31 and 0.35, respectively, when calculated for the K-Omega-SST turbulence model and the Spalart-Allmaras turbulence model at an AOA of 25°. The flow visualization results revealed that there is a single flow separation due to modified leading edge from sharp to blunt, thus flow complexity is reduced.